Electrochemical impedance spectroscopy studies of stainless steel corrosion by two strains marine sulfate reducing bacteria - Nawawi, M.F; Sahrani, F.K; Usup, G; Ahmad, A; Wan Muda, W.M.L; Isa, M.C. (University Kebangsaan Malaysia, 2012)
This research was conducted to compare corrosion potential of two strains of marine sulfate reducing bacteria (SRB1 and SRB2) on their effect of biocorrosion on stainless steel AISI304 using electrochemical techniques. This study was carried out using Electrochemical Impedance Spectroscopy (EIS) to determine the impedance value (passivity, Rp) and corrosion rate. An electrochemical measurement showed that the value of Impedance for Stainless steel in SRB culture is much smaller compare to VMNI medium (control), indicating a degradation of metal was occurred. SRB2 showed more aggressiveness on corrosion compare to SRB1 as the impedance value, Rp of stainless steel in SRB2 culture is lower compare to SRB1. In conclusion, EIS techniques given a good results to study mechanisms of corrosion and surface passivity.